Chemistry of ODP Hole 121-752B samples (Table 2) - Schuraytz, B C; O'Connell, S O; Sharpton, V L (Supplement to: Schuraytz, BC et al. (1991): Data report: iridium and trace element measurements from the Cretaceous-Tertiary boundary, Site 752, Broken Ridge, Indian Ocean. In: Weissel, J; Peirce, J; Taylor, E; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 121, 913-919, https://doi.org/10.2973/odp.proc.sr.121.175.1991, 1991)
Fourteen samples spanning a 2.5 m interval that includes the Cretaceous-Tertiary (K/T) boundary from Hole 752B near the crest of Broken Ridge in the eastern Indian Ocean, were studied in order to search for anomalous enrichments of iridium (Ir) and shock-metamorphosed quartz grains. No allogenic quartz grains >10 µm were observed, hence the presence of quartz containing diagnostic evidence of shock-metamorphism could not be confirmed. Two Ir anomalies of 2.2±0.6 and 2.0±0.4 parts per billion (ppb) were measured in samples of dark green ash-bearing chalk at depths of 357.93 and 358.80 mbelow seafloor (mbsf), respectively, (Samples 121-752B-11R-3, 13-14 cm, and 121-752B-11R-3, 100-101 cm) using conventional Instrumental Neutron Activation Analysis (INAA). These samples containing anomalous enrichments of Ir were taken from approximately 82 cm above and 5 cm below the extinction level of Globotruncanids. Our results are consistent with those of Michel et al. (this volume), who observe elevated concentrations of Ir at these depths in addition to a larger Ir anomaly associated with the extinction level of Globotruncanids.